1999
DOI: 10.1175/1520-0493(1999)127<2709:tuamoc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Misuse of Conditional Symmetric Instability

Abstract: A commonly employed explanation for single-and multiple-banded clouds and precipitation in the extratropics is slantwise convection due to the release of moist symmetric instability (MSI), of which one type is conditional symmetric instability (CSI). This article presents a review of CSI with the intent of synthesizing the results from previous observational, theoretical, and modeling studies. This review contends that CSI as a diagnostic tool to assess slantwise convection has been, and continues to be, misus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(183 citation statements)
references
References 122 publications
5
177
0
1
Order By: Relevance
“…We also used u e and u e * (saturated equivalent potential temperature) in the stability calculation, as discussed in Schultz and Schumacher (1999), and the results were almost identical, likely because the PV g is assessed in the upper troposphere, where the low absolute moisture content results in only slight differences in the three versions of potential temperature.…”
Section: B Evolution Of the Environment And Convection Prior To Mcs mentioning
confidence: 99%
“…We also used u e and u e * (saturated equivalent potential temperature) in the stability calculation, as discussed in Schultz and Schumacher (1999), and the results were almost identical, likely because the PV g is assessed in the upper troposphere, where the low absolute moisture content results in only slight differences in the three versions of potential temperature.…”
Section: B Evolution Of the Environment And Convection Prior To Mcs mentioning
confidence: 99%
“…Browning (2004) and Clark et al (2005) suggested that the slantwise circulations in the cloud head may have been caused by the presence of conditional symmetric instability (CSI) (see Schultz and Schumacher (1999) for a review of CSI) by consistency with the scale of the circulations. Thus, they hypothesized, the release of CSI may play a role in the generation of the sting jet.…”
Section: Banding In the Cloud Headmentioning
confidence: 99%
“…A thorough review (together with a rich reference list) of different types of SI and the 'use and misuse' of them appears in Schultz and Schumacher (1999). Theoretical treatment of linear SI dynamics (Stone, 1966(Stone, , 1970Hoskins, 1974;Bennetts and Hoskins, 1979;Emanuel, 1983a,b;Xu, 1986a,b) focused mainly on normal mode analysis, in which attention was focused on the necessary Richardson number condition for instability, and on the largest modal growth rate as a measure of the potential for occurrence of slantwise convection.…”
Section: Introductionmentioning
confidence: 99%